CHALLENGES AND PROSPECTS FOR AFFORDABLE AND SUSTAINABLE HOUSING: THE CASE OF YOLA, NIGERIA - Muazu, Jallaludeen; Oktay, Derya (Open House Int, 2011)
This paper aims to determine the challenges and prospects for affordable housing within the context of sustainability by investigating the socio-economic and environmental impacts of housing developments based on the analysis of four so-called affordable housing schemes in Yola, Nigeria. Using questionnaire survey and indicators developed from literature reviews on affordable and sustainable housing, the findings suggest that due to inadequate availability of housing inputs (land, finance, infrastructure, labor and materials), lack of diversity, improper location, inefficient transport facilities and lack of user participation, the examined developments are neither sustainable nor affordable. The research hence contributes some empirical evidence to overcome the defined shortcomings and provides a basis for governments' housing commitments towards reforming and devising policies for community involvement in housing provision, providing easy access to land with legal title deeds, easy access to housing finance, infrastructure, etc.
Keywords: Urbanization; Affordable Housing; Sustainable Development; Yola; Nigeria